State and Trait Rumination Effects on Overt Attention to Reminders of Errors in a Challenging General Knowledge Retrieval Task - Whiteman, Ronald C.; Mangels, Jennifer A. (Frontiers in Psychology, 2020)
Rumination is a recurrent and repetitive manner of thinking that can be triggered by blockage of personally-relevant goals, creating a temporary state of abstract and evaluative self-focus. Particularly when focused on passive “brooding” over one’s problems and feelings, however, rumination can increase negative affect, interfere with problem-solving, and through a negative feedback cycle, become a chronic trait-like style of responding to personal challenges, particularly in women. Given the pervasiveness of rumination and its potential impact on cognitive processes and emotional states, the present study asks how it impacts attention to feedback that either reminds individuals of goal-state discrepancies (reminders of errors) or could help to remediate them (corrective information). Using eye-tracking, we examined both state and trait rumination effects on overt measures of attention (first fixation duration [FFD] and total fixation duration [TFD]) during simultaneous presentation these two types of feedback following failed attempts to answer challenging verbal general knowledge questions (average accuracy ~30%). After a pre-induction baseline, we induced either a state of rumination using a series of writing exercises centered on the description of an unresolved academic concern or a state of distraction by centering writing on the description of a neutral school day. Within our sample of women-only sample, the Rumination condition, which writing analysis showed was dominated by moody brooding, resulted in some evidence for increased initial dwell time (FFD) on reminders of incorrect answers, while the Distraction condition, which did not elicit any rumination during writing, resulted in increased FFD on the correct answer. Trait Brooding augmented the expression of the more negative, moody brooding content in the writing samples of both induction conditions, but only influenced TFD measures of gaze duration and only during the pre-induction baseline, suggesting that once the inductions activated Rumination or Distraction states, these suppressed the trait effects in this sample. These results provide some support for attentional-bias models of rumination (attentional scope model, impaired disengagement hypothesis) and have implications for how even temporary states of rumination or distraction might impact processing of academic feedback under conditions of challenge and failure.